Multi-omics evaluation of peritoneal fluid in gastroesophageal cancer (OMEGCA): protocol for a prospective multicentre cohort study to detect occult peritoneal metastases in patients undergoing curative-intent treatment - David S. Liu; Zexi Allan; Jeanne Tie; Katheryn Hall; Margaret M. Lee; Darren J. Wong; Stephen Q. Wong; Niall C. Tebbutt; David I. Watson; Markus Trochsler; Krinal Mori; Nicole Winter; et al. (PLoS ONE, 2025)
Introduction Early detection of peritoneal disease, especially micro-metastases, in patients with gastroesophageal adenocarcinoma is critical as it alters therapeutic intent, providing a vital opportunity to personalise treatment. However, our ability to accurately stage the peritoneum is inadequate. Tumour-derived DNA in peritoneal lavage fluid (ptDNA) has been suggested to be more sensitive than current methods to stage the peritoneum. Accordingly, this study will determine whether ptDNA is a biomarker of peritoneal micro-metastasis and evaluate its prognostic value in patients with gastroesophageal adenocarcinoma undergoing curative-intent treatment. Methods and analysis This will be an Australian multi-centre prospective observational cohort study enrolling patients undergoing routine staging laparoscopy and subsequent curative-intent treatment (either upfront surgery or perioperative chemo-/radiotherapy and surgery) for gastric and gastroesophageal junction adenocarcinoma. Tumour biopsies, blood and peritoneal lavage fluid will be collected at the time of staging laparoscopy for all patients. A subset of patients will have blood and peritoneal fluid collected at the time of surgical resection, and blood collected at the first post-operative clinic. These biospecimens will undergo genomic and methylomic analysis to detect tumour DNA. ptDNA status will be correlated to disease free survival, peritoneal-specific event free survival, overall survival, sites of treatment failure, histopathological features, and peritoneal lavage cytology status. Registration This study is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12624000451505p).